Biodistribution and radiation dosimetry of the positron emission tomography probe for AMPA receptor, [11C]K-2, in healthy human subjects - Hatano, Mai; Miyazaki, Tomoyuki; Ishiwata, Yoshinobu; Nakajima, Waki; Arisawa, Tetsu; Kuroki, Yoko; Kobayashi, Ayako; Takada, Yuuki; Ogawa, Matsuyoshi; Kawamura, Kazunori; Zhang, Ming-Rong; Higuchi, Makoto; et al. (Scientific reports, 2021)
[ 11 C]K-2, a radiotracer exhibiting high affinity and selectivity for α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs), is suitable for the quantification of AMPARs in living human brains and potentially useful in the identification of epileptogenic foci in patients. This study aimed to estimate the radiation doses of [ 11 C]K-2 in various organs and calculate the effective dose after injection of [ 11 C]K-2 in healthy human subjects. Twelve healthy male subjects were registered and divided into two groups (370 or 555 MBq of [ 11 C]K-2), followed by 2 h whole-body scans. We estimated the radiation dose of each organ and then calculated the effective dose for each subject. The highest uptake of [ 11 C]K-2 was observed in the liver, while the brain also showed relatively high uptake. The urinary bladder exhibited the highest radiation dose. The kidneys and liver also showed high radiation doses after [ 11 C]K-2 injections. The effective dose of [ 11 C]K-2 ranged from 5.0 to 5.2 μSv/MBq. Our findings suggest that [ 11 C]K-2 is safe in terms of the radiation dose and adverse effects. The injection of 370–555 MBq (10 to 15 mCi) for PET studies using this radiotracer is applicable in healthy human subjects and enables serial PET scans in a single subject.